Avengers Assemble! Critical Perspectives on the Marvel Cinematic Universe, Terence McSweeney (2018). Issue 1 (1st March 2022) - Goodrum, Michael
Review of: Avengers Assemble! Critical Perspectives on the Marvel Cinematic Universe, Terence Mcsweeney (2018)New York: Wallflower Press, 310 pp., ISBN 978-0-23118-625-4, h/bk, £81, p/bk, £25